IL-2 Receptor Antagonist (Basiliximab) Is Associated with Rapid Fibrosis Progression in Patients with Recurrent Hepatitis C after Liver Transplantation Using Serial Biopsy Specimens - Hanouneh, I. A. (Avicenna Organ Transplantation Institute, 2010)
Background: Recurrence of hepatitis C virus (HCV) infection following orthotopic liver transplantation (OLT) is universal. There is paucity of data on the safety and efficacy of interleukin (IL)-2 receptor antagonist (IL-2RA) when added to the standard immunosuppression regimen in OLT recipients with recurrent HCV infection. Objectives: To evaluate the efficacy of IL-2RA (Basiliximab) in preventing acute cellular rejection (ACR) in patients with recurrent HCV infection after OLT and to assess the impact of IL-2RA in promoting fibrosis progression in post-OLT recurrent HCV infection. Methods: Using an electronic pathology database, we identified all OLT/HCV patients with at least 2 post-OLT liver biopsies (1998–2006). Standard immunosuppression consisted of steroids and calcineurin inhibitor with and without mycophenolate mofetil. All patients who were transplanted after May 2004 received IL-2RA induction therapy. The Ludwig-Batts system was used to stage all biopsies (593 biopsies from 124 patients). The first biopsy that showed post-OLT fibrosis or the last follow-up biopsy was used for time-to-progression analysis. Univariate and multivariate Cox proportional hazards regression analyses were performed to identify factors associated with the progression of fibrosis. Results: ACR was significantly (p<0.001) lower in patients who received IL-2RA (20 of 70, 29%) compared to those who did not (33 of 54, 61%). The median (25%ile, 75%ile) follow-up was 12.1 (6.1, 23.9) months during which 61% of patients had progression of fibrosis. Univariate analysis revealed that a higher HCV RNA load at 4 months post-OLT (p=0.002), cytomegalovirus (CMV) infection (p<0.001), use of steroid therapy for ACR (p=0.043), and use of IL-2RA (p<0.001) were associated with higher hazards for the progression of fibrosis. Viral load at 4 months post-OLT was significantly (p=0.025) higher in patients who had IL-2RA therapy (median [25%ile, 75%ile]: 2.9 [1.0, 5.0] ×10(6 ) vs. 1.4 [1.0, 2.3] ×10(6)). In multivariate analysis, patients who received IL-2RA therapy were 3.1 (95% CI: 1.8–5.3) times more likely to develop fibrosis than those who did not treated with IL-2RA. Steroid therapy for ACR remained significantly (Hazard Ratio=2.9, p=0.002) associated with the progression of fibrosis. Conclusion: IL-2RA (Basiliximab) decreases the rate of ACR. However, it may be associated with more rapid histological progression of the disease in post-OLT recurrent HCV.